Efficiency and complexity in grammars - Hawkins, John A. (Oxford linguistics., 2004)
John Hawkins demonstrates a clear link between how languages are used and the conventions of their grammars. He sets out a theory in which performance shapes grammars and accounts for the variation patterns found in the world's languages.